Restriction Mapping of MC4R Gene on Bali Cattle (Bos sondaicus) as Genetic Marker for Breeding Program in Compared to Bos taurus and Bos indicus - Yoga Cipta Perdana; Tety Hartatik (Universitas Gadjah Mada, 2022)
MC4R is a gene that has potential effects on growth traits such as body weight and feed intake. The usage of single nucleotide polymorphism (SNPs) in melanocortin-4 receptor (MC4R) as selection markers could help achieve effectiveness in the breeding program. This study aimed to analyze the restriction mapping based on SNPs in the MC4R gene for Bali cattle (Bos sondaicus) compared to various breeds of cattle. Partial MC4R gene was amplified using a primer (F: 5’-ACC AAT GTC AGT GAG TCC CC- 3’ and R: 5’-CTT CAT GTT GGC GCC CTG-3’) with a polymerase chain reaction (PCR) method. Genotype and allele frequencies were calculated using Chi-Square test and analyzed with Hardy–Weinberg law. Restriction enzyme was analyzed using Nebcutter V.2 to see the association between SNPs and the recognition site of restriction enzyme. The result showed four SNPs g.554 T>C, g.634 G>T, g.673 C>T, and g.742 G>A were found in the exon region. SNP g.742 G>A was found as a heterozygote genotype and the rest are SNP g.554 T>C, g.634 G>T, and g.673 C>T were found as homozygote genotypes. All SNPs were synonymous which did not change the amino acid translated. Three restriction enzymes were identified as MmeI, TspRI, and BsrI which attach to SNPs g.554 T>C, g.634 G>T, and g. 742 G>A respectively. SNPs found notably g. 742 G>A can be used as genetic markers associated with growth traits for further research on Bali cattle.